Measuring leadership language: faculty leadership LIWC dictionary validation study - Rizzuto, Tracey E.; Manongsong, Ague Mae; St Aubin, Ally; Jeong, Shinhee; Spitzmueller, Christiane; Madera, Juan M. (Frontiers in Education, 2025)
IntroductionThis two-part multimethod study develops and validates a Faculty Leadership Linguistic Inquiry Word Count (FL-LIWC) dictionary for use in university settings.MethodologyIn Study 1, an integrative literature review centered on Yukl’s (2012) hierarchical taxonomy of leadership behavior and Delphi panels are used to establish a four-component definition of Faculty Leadership and to generate a 354-word LIWC dictionary reflecting leadership behaviors performed by university faculty. Study 2, exploratory, confirmatory, and structural path models using textual data extracted from external review letters (ERLs) from 981 promotion and tenure cases across five universities is employed to conduct a multi-step validation analysis of the dictionary’s accuracy, nomological network and potential for gender difference.ResultsThis study demonstrates that FL-LIWC is a theoretically coherent and empirically robust tool for measuring faculty leadership and is relatively free of potential biases associated with gender difference.DiscussionIt provides greater understanding of how linguistic reflections in ERL text may be used in university setting to provide additional insight into leadership behaviors that are of emerging importance to faculty performance assessment and academic advancement decisions.